PEMBELAJARAN TEMATIK (METODOLOGI DALAM ISLAM) - Sedya Santosa; Zahratul Fitria (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The basic concept of thematic learning is learning through a methodology in Islam. This scientific work aimed to reveal the basic concept of contextual or thematic learning using a method in Islamic perspective and why thematic learning became a learning concept for elementary school children and madrasah children. In this study, researchers used Library Research (Literature) research. The data were collected through documentation. The data analysis method in this study was content analysis. This study explained how (1) the thematic learning concept as a methodology in Islam based on the Quran was stated in surah al- baqarah verse 129 and verse 151, explaining that learning integrated an understanding for skills, knowledge, integrity, attitude, and character. (2) the thematic learning was certainly very appropriate to be applied to elementary school children or madrasah ibtidaiyah children in which thematic learning was a derivative of the concept of science in Islam or often referred to as (Wahdah Al-ulum) or known as the integration of science, assimilation of science, objectifies of science, and interconnection of science. (3) Integrated thematic learning was applied, all of which were seen from various aspects of the learner's cognitive, affective, and psychomotor aspects of the learner itself. This research was expected to be used by furtherresearchers as one of the additional information to conduct research using literature studies to facilitate improving a study that will be studied.